If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5 = 8x + 5 Reorder the terms: -5 + 3x = 8x + 5 Reorder the terms: -5 + 3x = 5 + 8x Solving -5 + 3x = 5 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -5 + 3x + -8x = 5 + 8x + -8x Combine like terms: 3x + -8x = -5x -5 + -5x = 5 + 8x + -8x Combine like terms: 8x + -8x = 0 -5 + -5x = 5 + 0 -5 + -5x = 5 Add '5' to each side of the equation. -5 + 5 + -5x = 5 + 5 Combine like terms: -5 + 5 = 0 0 + -5x = 5 + 5 -5x = 5 + 5 Combine like terms: 5 + 5 = 10 -5x = 10 Divide each side by '-5'. x = -2 Simplifying x = -2
| 20x+5=15x+25 | | 4n-12=12n-4 | | 11n=10n+16 | | 2x+58=6x-10 | | -5(3x+4)=4x+16-7x | | 0.3x-0.5x+3=-4 | | -4x-5x= | | 9n-34=6n+5 | | m+(-5)=19 | | 5(x+4)=6(3x-2) | | 4y+xy=11 | | .75a+14=8 | | 2(1-2b)+2(1+5b)=-9+6b | | (x^4)+(41x^2)+400=0 | | 6p+(p-4)=4p | | 264-3x=42x+19 | | -36x^4+25x^3-4= | | h+(-9)=-9 | | (x^4)+(4x^2)+400=0 | | 15t+9=5t+9 | | 5b-12=14 | | 9(x-4)=72 | | -10y-7=6y+9 | | d-15=44 | | -441=4(-8n-4) | | 2(8x+2)=3(2x-7) | | 5x+2x=6x-2 | | 5x-6(3x+4)=9(x-6)+3 | | -9x+4x+15-10x= | | 7u^2-48u-7=0 | | 0.02-0.02(x+2)=-0.04(2-x) | | 6x+6=4x+2 |